The tetralogy of loneliness: an introduction to the narrative of Javier Tomeo - Pozuelo Yvancos, José María (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
This essay analyzes four novels of Javier Tomeo. He is one of the most significant narrators of the Spanish "new narrative". In the context of the general lines of this narrative, the author stands out in the novels of Tomeo some particulars profiles which permit him qualifies the four novels El castillo de la carta cifrada, Amado monstruo, El cazador de leones, and La ciudad de las palomas like a "tetralogy of loneliness". He analyzes the intertextuality of the four works, his principal subjects and in especial makes an analysis of the narratology of the discourse, with especial insistence in the "récit de paroles" and in the formulas of the direct style, techniques in which Javier Tomeo has shown a great originality.